Territorialidade rural e repartição do ICMS: o caso do Estado do Paraná - Luci Nychai; Felipe Polzin Druciak (Confins)
The Brazilian territoriality policy is a strategy of vertical cooperation for the development of economically fragile spaces, and in turn adds sine qua non conditions to enjoy tax returns. In order to assess this premise, this article aimed to analyze in a comparative way the distribution of part of the 25% portion of the tax on operations related to the movement of goods and on services of interstate, intermunicipalitie and communication services (ICMS) Whether or not the municipality belongs to the rural territory. The ICMS is the main tax collected at the state level, whose share of 75% is with the State and 25% return to the Municipalities based on the Municipal Participation Index (MPI). The factor generating the ICMS is the final price composed by the value added. However, each state has the autonomy to create its own criteria for parameterizing the MPI. Paraná is the state that most incorporated rural parameters in the composition of the IPM. For this study, the empirical analysis was based on cross section data for the 399 Municipalities of the State of Paraná, located in the southern region of Brazil. The analysis was based on the ICMS revenue forecast for 2017 on which the Ordinary Least Squares Robust (OLS) was applied whose control variable defined by Dummy "municipality belongs to rural territory = 1" and "municipality not belonging = 0 ". The results showed that there is a gain for the Municipalities of Paraná, inserted in the rural territory, regarding the receipt of revenue from part of the 25% portion of the ICMS due to the insertion of rural parameters in the composition of the Municipality Participation Index (MPI) such as agricultural production, rural population and rural properties..